Organisational culture and knowledge creation : the relationship between knowledge creation enablers and organisational culture types - Khanyile, Dumisani (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2009.